The Convergence Study on Korean Consumers’ Perception of Cosmeceuticals in the Aging Society (Medico Legal Update, 2019)
Background/Objectives: This study is aimed to investigate consumers’ interests in cosmeceuticals andto examine usage and satisfaction in the aging society. Therefore, it provides effective marketing data toindustries.Method/Statistical Analysis: For this study, self-questionnaires were done for Korean consumers who arein age over 20. A total of 366 copies were collected for the final analysis, and the data were analyzed bySPSS ver. 21.0 statistical program, then data were verified at the significance level of p